2019
DOI: 10.2174/1874220301906010064
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Insight of the Anti-inflammatory Effects of Curcumin with the Assessment of Parameters, Sources of ROS and Associated Mechanisms

Abstract: Background: Curcumin is an active constituent of Curcuma longa, which belongs to Zingiberaceae family. It is derived from the Rhizome of a perennial plant having molecular formula C21H20O6 and chemically it is (1, 7- bis (4- hydroxy - 3 methoxyphenyl) -1, 6 - heptadine - 3, 5 - diene), also known as diferuloylmethane. Curcumin has been extensively used as a herbal constituent for curing several diseases and is scientifically proven to show major effects as an anti-inflammatory agent. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 90 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Nutrients 2020, 12, 118 25 of 32 oxidative stress. In addition, gluconeogenesis was reduced, while glucokinase activity and glucose-6-phosphate levels were increased with curcumin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrients 2020, 12, 118 25 of 32 oxidative stress. In addition, gluconeogenesis was reduced, while glucokinase activity and glucose-6-phosphate levels were increased with curcumin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has the potential to attenuate inflammatory and oxidative stress diseases through increased antioxidant activities. A systematic and meta-analysis review by Wal et al (2019) [118], found that curcumin blocked the oxidation process in mitochondria and reduced ROS and cytokine production and increased the activities of antioxidant enzymes [118]. Although increased antioxidant intake, such as curcumin, has been traditionally thought to result in increased health [118][119][120], this concept has been recently challenged [121,122].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its weaknesses are low water solubility, low absorption from the gastrointestinal tract, poor stability in body fluids, rapid metabolism, and rapid clearance. For these reasons, its therapeutic use in medicine is limited, but great efforts have been made for a long time to investigate suitable usable nanoformulations [ 153 , 154 , 155 ]. Due to the huge number of such described nanoformulations (e.g., Figure 5 ), the overview of which would require a separate paper, only a few reviews or recently published important articles are listed here [ 78 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 ].…”
Section: Designed Nanoddssmentioning
confidence: 99%
“…In fact, the rhizome of the C. longa Linn plant contains curcumin. The role of curcumin as a free radical scavenger has been demonstrated in numerous studies [ 14 , 15 ]. Particularly in the testicular tissue, it can constrain the generation of ROS and nitric oxide in macrophages [ 16 ].…”
Section: Introductionmentioning
confidence: 99%